Arginine Needs of the Chick and Growing Broiler - Corzo, A.; Kidd, M.T. (International Journal of Poultry Science, 2003)
Two studies were conducted to evaluate Arg responses in broilers. The first study evaluated the Arg need of the female broiler for the period between 21 and 35 days of age. A control diet resembling industry guidelines contained (1.35% Arg). The test diet was formulated to contain 0.95% dietary Arg. Progressive increments of 0.10% Arg at the expense of a filler created the different experimental treatments. No significant trends were observed for the variables analyzed. All dose-response treatments did not differ from the control diet. Based on the lack of response from the first study, a second study was designed to focus on Arg responses at an earlier age (0-18 days). Progressive increments of 0.12% Arg at the expense of a filler created the different experimental treatments. Males optimized body weight gain at 1.15% dietary Arg, while feed conversion required more Arg for optimization (1.28%). Mortality was not influenced by dietary Arg. Data indicated that the chick has considerably acute need for dietary Arg at an earlier age possibly associated with immune system development and early microbial challenges.